Evaluasi Kebijakan Dana Desa Untuk Kesejahteraan Masyarakat di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Setiawan, Dedi; Lubis, Yurial Arief (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This study aims to evaluate the effectiveness of the Village Fund policy in improving community welfare in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency. The Village Fund is a government program that aims to support infrastructure development, economic empowerment, and the improvement of public services at the village level. This study uses a qualitative method with a descriptive approach, where data is collected through observation, in-depth interviews, and documentation. The informants consist of village officials and the community who have experience in managing the Village Fund. The results of the study show that the Village Fund policy has had a positive impact on infrastructure development, such as the improvement of village roads and public facilities, as well as in economic empowerment through business capital assistance and skills training. However, the effectiveness of this policy still faces obstacles, such as limited capacity of village officials, lack of transparency in budget management, and low community participation in supervision. Therefore, it is necessary to increase the capacity of the apparatus, technology-based transparency, and community involvement so that the management of the Village Fund is more optimal and sustainable.